2011
DOI: 10.1634/theoncologist.2011-0064
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Status at 12 Weeks Predicts Survival in Advanced Colorectal Cancer: Findings from NCCTG N9741

Abstract: Bristol-Myers Squibb; and ownership interest with Tetralogic Pharmaceuticals. Reviewers "A" and "B" disclose no financial relationships. The content of this article has been reviewed by independent peer reviewers to ensure that it is balanced, objective, and free from commercial bias. On the basis of disclosed information, all conflicts of interest have been resolved. LEARNING OBJECTIVESAfter completing this course, the reader will be able to:1. Explain the difference in survival prediction between response cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…30, 31 Although these results might seem to contradict ours given the overlap in the source data, the methodology differed in that they used landmark analyses to measure associations with OS. The resampling approach used in our study does not test how well end points associate with OS, but rather how powerful they are for making the correct go/no-go decision at the end of phase II.…”
Section: 27mentioning
confidence: 80%
“…30, 31 Although these results might seem to contradict ours given the overlap in the source data, the methodology differed in that they used landmark analyses to measure associations with OS. The resampling approach used in our study does not test how well end points associate with OS, but rather how powerful they are for making the correct go/no-go decision at the end of phase II.…”
Section: 27mentioning
confidence: 80%
“…There was a statistically significant difference between CR/PR and SD status for patients with colorectal cancer based on the 12-and 24-week landmark analyses, thus lending support to the use of the TriTR metric as reported previously. 7,11 The RECIST definition for SD does not distinguish patients with true SD from those with a minor increase or minor decrease. The TriTR metric puts SD patients into their own category unlike the DiTR or the DCR metrics.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] For example, nonprogression rate or the disease control rate (DCR) classifies patients who achieve SD for an extended period of time as a success, in addition to those who achieve complete response (CR) or PR. DCR was shown to be superior to response rate in predicting survival in the setting of non-small-cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, early tumour shrinkage (ETS), usually defined by a relative (per cent) reduction in tumour size at a certain time point, has garnered attention as an important clinical marker associated with long survival in the treatment of mCRC. [5][6][7] Several studies [8][9][10][11][12][13][14][15][16][17][18] showed that achieving ETS during first-line treatments can predict improved OS, suggesting its potential use as a surrogate endpoint. 5 6 However, the definition of ETS is inconsistent in various studies with respect to time points and cut-off values.…”
Section: How Might This Impact On Clinical Practice?mentioning
confidence: 99%